Genome-wide shRNA screening identifies genes involved in fulvestrant resistance in breast cancer - Ramos, Pedro André Dias (2016)
Breast cancer accounts as the most prevalent cancer and the leading cause of cancer death worldwide among women. Estrogen is one main factor responsible for tumour growth in breast cancer patients through stimulation of estrogen receptor (ER) signalling. ER positive (ER+) breast cancer patients are eligible for anti-estrogenic drugs. Fulvestrant (Faslodex®) represents a second-line therapy for the treatment of postmenopausal women with ER+ advanced breast cancer. Unfortunately, a significant number of ER+ patients will develop resistance to second-line fulvestrant treatment. It is therefore important to understand the molecular mechanisms of resistance and to identify biomarkers capable of predicting response to this treatment. The aim of this project is to establish a genome-wide shRNA functional screening to identify key proteins central in resistance mechanisms and potentially predictive biomarkers capable of identifying ER+ patients that are responsive or resistant to fulvestrant treatment. To do so, a MCF-7-based fulvestrant resistant breast cancer cell line was used. MCF-7/LCC1 and MCF-7/LCC9 were transduced with shRNA libraries covering over 15,000 mRNAs and treated with fulvestrant. This led to depletion and/or enrichment of shRNAs targeting genes evaluated by next generation sequencing (NGS). Deconvolution of NGS data from genomic DNA of LCC1 and LCC9 cells transduced by shRNA libraries led to identification of 206 genes that may have functional significance in fulvestrant resistance. Ingenuity Pathway Analysis of the candidate genes identified HSD17B10 and HSPE1 as key-molecules in networks related to cell proliferation and death. We have found that these genes are upregulated in different fulvestrant-resistant cell lines when compared to their fulvestrant-sensitive parental cell line at gene and protein expression levels using RT-qPCR and Western blotting. This expression is enhanced in fulvestrant presence, suggesting that these proteins may have critical importance in the resistance phenotype. Further studies on these proteins may elucidate on how to overcome fulvestrant resistance.